2016
DOI: 10.1111/jpn.12578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo feeding with glycerol for broilers

Abstract: The objective was to evaluate the effect of in ovo feeding with glycerol on post-hatch development in broiler chicks. A total of 408 fertile eggs were divided into six experimental groups consisting of five 0.9% saline solutions containing various concentrations of glycerol (12.5, 25.0, 37.5 and 50.0 nmol/ml), and a placebo group (inoculation with saline only) and a control group (without inoculation). Inoculations were performed at 17 days of incubation for the evaluation of hatchability, embryo mortality, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
14
1
1
Order By: Relevance
“…These results suggest that glycerol could be used as an IOF ingredient up to 12 mg/ml, with no deleterious effects on incubation or hatching parameters. However, the results obtained in the present study are not consistent with the findings of Neves et al (), who observed reduced HF and higher embryo mortality when eggs were injected with 2.3 and 4.6 μg glycerol/ml; however, it should be noted that these doses were much lower than those tested in the present study. In addition, the present study did not include a non‐injected group, which would allow evaluating the effect of the IOF technique.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results suggest that glycerol could be used as an IOF ingredient up to 12 mg/ml, with no deleterious effects on incubation or hatching parameters. However, the results obtained in the present study are not consistent with the findings of Neves et al (), who observed reduced HF and higher embryo mortality when eggs were injected with 2.3 and 4.6 μg glycerol/ml; however, it should be noted that these doses were much lower than those tested in the present study. In addition, the present study did not include a non‐injected group, which would allow evaluating the effect of the IOF technique.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, hatchling RYSW was used as an indication of transference of yolk sac nutrients; however, glycerol IOF did not decrease yolk sac absorption in neither of the experiments. This result was unexpected, considering literature reports, such the lower yolk sac utilization observed by Zhai, Gerard, Pulikanti, and Peebles (), when broiler breeder eggs received IOF of different simple carbohydrates, and the heavier yolk sacs of hatchlings inoculated in ovo with glycerol by Neves et al (). Nevertheless, according to Uni, Yadgary, and Yair (), fresh yolk sac weight may provide an inaccurate indication of yolk sac utilization, because there may be an influx of water and protein from the albumen to the yolk sac.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…17th day Amnion The different levels of glycerol increased the activity of liver glycerol kinase, weights of spleen and heart. 68 Glycerol Late stage Chorioallantoic fluid…”
Section: 5-19 Daysmentioning
confidence: 99%